What is China? : Territory, Ethnicity, Culture, and History - Zhaoguang, Ge; Translated by Hill, Michael Gibbs (London The Belknap Press of Harvard University Press, 2018)
Chinese natives rarely attempt to explain their country to outsiders; everything they know is China, and everyone they know is Chinese. China is so all-absorbing that the idea of helping foreigners understand its customs, traditions, and history seems pointless. In this book, Ge Zhaoguang has undertaken the task of explaining China to foreigners. He examines the historical and cultural background of China's emergence as a major world power from a Chinese perspective. Ge argues that the meanings of China and Chinese culture regularly change and avoid a single definition, and that honest discussion of these different meanings and how they arose give us a better route to understanding both historical and contemporary China. He puts forward his solution as an alternative to what he sees as writings that are too eager to deconstruct and perhaps dismiss the idea of China as a historical entity altogether. By offering a general scholarly overview of China, Ge's book begins to overcome the disjunction between American knowledge about China and Chinese understanding of the country
Include Index
Keywords: Diplomatic relations -- National characteristics, Chinese -- Boundaries